The Reliability of Witness Testimony in Violent Crimes in the Context of Post-Traumatic Stress Disorder: An Analytical Study Through legal practices - Abdelaziz, Dalia Kadry Ahmed (Journal of Ecohumanism, 2025)
This analysis explores the ways post-traumatic stress disorder (PTSD), could affect the accuracy of testimony in violent crimes. This research examines the link between the psychological trauma, that may be experienced by witnesses at the time, or in the aftermath of the crime itself, their ability to provide accurate and reliable testimony in subsequent legal action. The study relies on legal and psychological literature to examine how PTSD alters perception and memory, and how that might affect the accuracy of testimony in criminal cases. The paper looks at the ways that the legal systems in the US and UK deal with testimony altered by psychological trauma. In the USA, court trials use a PTSD impact assessment for witnesses to evaluate their ability to provide correct testimony. The courts in the United Kingdom are encouraged by guidance to consider psychological effects on testimony in criminal matters involving psychological trauma. The study will also cite an international legal framework for addressing the effects of PTSD on testimony, including United Nations standards that urge courts to implement trauma-sensitive practices to achieve justice